Greek fire [videorecording]. ([S.l.] Transatlantic Films Production, 1989)
Explores the influences of ancient Greece on our lives today.
Pt.1. Source: Know thyself (26 min.) -- Pt.2. Myth: the gods below (27 min.)
VHS.
Part I. Writer, Jonathan Stamp; director and producer, Reuel Guest, Jonathan Stamp; narrator, Juliet Stevenson; Part 2. Writer, Roger Parsons; producer, Reuel Guest; narrator, Juliet Stevenson.
Keywords: Civilization, Western; Greek influences; Mythology, Classical -- Mythology, Greek; Greece -- History; HUMANITIES; EUROPEAN HISTORY; HISTORY